Providing Data Sharing For Multiple Users In Cloud (International Journal of Engineering and Computer Science, 2014)
With the character of low maintenance, cloud computing provides a cheap and economical resolution for sharing cluster resource among cloud users. Sadly, sharing information an exceedingly in a multi-owner manner whereas protective information and identity privacy from an untrusted cloud continues to be a difficult issue, because of the frequent modification of the membership.During this paper, we tend to propose a secure multi-owner data sharing theme, named Mona, for dynamic teams within the cloud. By investing cluster signature and dynamic broadcast encryption techniques, any cloud user will anonymously share information with others. Meanwhile, the storage overhead and cryptography computation price of our theme area unit freelance with the quantity of revoked users. Additionally, I tend to analyze the protection of our theme with rigorous proofs, and demonstrate the potency of us theme in experiments.